Hind Brain in Mature Cystic Teratoma Ovary: A Case Report - Shrestha, Joon; Chapagain, Ashok; Rana Gurung, Sarita; Bastakoti, Shankar (Annapurna Journal of Health Sciences, 2024)
Mature cystic teratoma is the commonest benign neoplasm occurring in the ovary, comprising for 27-44% of all ovarian tumors and most cases in reproductive age women. Here we report the case a 26-year-old female presented with complain of lower abdominal pain for six months which on ultrasound evaluation and Computed Tomography showed dermoid cyst measuring 7x5.3x5 cm with non-enhancing soft tissues predominantly containing fat and few calcifications. Microscopic examination showed a cyst wall lined with stratified squamous lining including adnexal structures (sebaceous glands) and glial tissue, along with a focal area lined by respiratory epithelium. There was no immature component. Well-differentiated cerebellum within ovarian teratoma is extremely rare entity in literature